The future of the liberal order: the key questions - Anheier, Helmut K. (Routledge Taylor & Francis Group, 2022)
This book brings together some of the finest minds of social science to answer the great questions about the future of the liberal order. With contributions from the world of economics, sociology, political science, management, international relations and the humanities, this book provides a unique series of insights. Chapters explore the great questions of our time as they relate to the future of the liberal international and domestic order. Contemporary issues such as populisms, authoritarianism, trust and social cohesion, the future of global governance, finance, religion, and citizenship are addressed along with geopolitical implications and with a balance between expert authority and open-minded critique. It will be essential reading for students, scholars, and reflective practitioners across the human and social sciences.
Literaturhinweise, Register
Keywords: Globalisierung; Liberalismus